An Analysis of Translation Method Used by Angie Kilbane in “The Land of Five Towers” - Suliani, Dhea; Amalia Rakhmyta , Yunie; Shaumiwaty (New Language Dimensions, 2024)
This research aims to find out the method used by Angie Kilbane in translating the SL novel “Negeri 5 Menara” into TL “The Land of Five Towers” and what translation method is most dominantly used using Peter Newmark’s theory. This research uses a qualitative descriptive method with content. The research instrument in data collection is tabulation. The data will be analyzed using Miles and Huberman’s theory. This research data is in the form of SL sentences and TL sentences in the novel “The Land of Five Towers”. According to the research findings, Angie Kilbane by Peter Newmark employs word-for-word, literal translation, semantic translation, adaptation, free translation, idiomatic translation, and communicative translation. Just seven of the eight methods are employed by Angie Kilbane. Meanwhile, the faithful method is not employed because it is better suited for translating official writings and has a tendency to be more rigorous when translating novels. The research results show that the most dominant translation method used by Angie Kilbane is the literal translation method emphasizing to SL. SL is the first novel that must maintain elements of Indonesian culture so that readers in TL feel the aesthetic value of culture in SL. Literal translation also has a translation method that is not too far from TL because this method only adapts the grammar in the TL.